Modal decomposition of a fibre laser beam based on the push-broom stochastic parallel gradient descent algorithm - Chen, Fan; Zhao, Shubin; Wang, Qiang; Ma, Jun; Lu, Qiang; Wan, Jun; Xie, Renwei; Zhu, Rihong (Optics communications, 2021)
Compared with traditional methods, the stochastic parallel gradient descent (SPGD) algorithm used in modal decomposition has its own unique advantages of faster speed, wider application range, and low experimental effort, demonstrating many development prospects. However, the current SPGD algorithm only considers the modal weights of multimode optical fields and neglects the phase. More importantly, this algorithm is usually unsuitable for conducting modal decomposition of incoherent combined laser beams due to its serious ambiguities. In this paper, a novel modal decomposition algorithm, called the push-broom SPGD algorithm, is first proposed to achieve complete modal decomposition of optical fields emerging from multimode fibres. By iteratively evaluating the intensity profiles in different positions using the SPGD algorithm, this approach can obtain both amplitude and phase information with high accuracy. The proposed algorithm is preliminarily applied to the modal decomposition of an incoherent combined laser beam, and its feasibility is demonstrated via numerical simulations. By inserting a parallel plate, ambiguities can be solved and the influence of random noise is suppressed, demonstrating this algorithm’s potential. •Novel Modal decomposition algorithm, named push-broom SPGD algorithm, is proposed.•This algorithm obtains both amplitude and phase information with high accuracy.•This algorithm provides an access to the modal content of combined laser beam.•The proposed off-axis method solves the ambiguity problem perfectly.